Family Business: how family and ownership shapes business professionalization - Lissoni, Juliano; Pereira, Maurício Fernandes; Almeida, Martinho Isnard Ribeiro; Serra, Fernando Ribeiro (Review of Business Management, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> This article’s main purpose consists in showing how family and ownership cultures may influence the process of making a “well-performing” organization, based on an empirical study in family business in Brazil. The study aimed to find critical moments of company’s history and the focus was to compare critical moments with the three-dimension model of family business development proposed by Davis et al. (1996). Through facts sequence, research was organized so as to find how the process influenced company’s professionalization. The article concludes that family and its values and culture may impact on the evolution, and the first step to organize a company is to organize the family that leads the company. Key words: <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>Family business. Culture. Three-dimensional model. Business professionalization.